Hubungan Tingkat Pemahaman Perkembangan Kurikulum di Indonesia dengan Self-Regulated Learning Mahasiswa S2 Pendidikan Dasar - Hafsah Anas; Atep Sujana; Effy Mulyasari (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aimed to determine the relationship between the level of understanding of curriculum development in Indonesia and self-regulated learning among master’s students in elementary education. The study employed a quantitative correlational method. The sample consisted of master’s students selected through purposive sampling. Data were collected using questionnaires and analyzed with Pearson Product Moment correlation. The results showed a positive and significant relationship between understanding curriculum development and self-regulated learning (r = 0.598; p < 0.05). The higher the students’ understanding of curriculum development, the better their ability to regulate their learning independently.